Reply to Jalink, M.B. Comment on “Senthilkumaran et al. Bilateral Simultaneous Optic Neuritis Following Envenomations by Indian Cobra and Common Krait. Toxins 2022, 14, 805” - Subramanian Senthilkumaran; Stephen W. Miller; Harry F. Williams; Ponniah Thirumalaikolundusubramanian; Ketan Patel; Sakthivel Vaiyapuri (Toxins, 2024)
We thank the author for showing interest in our article [...]